If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5(8x + 2) = 18 + 2 Reorder the terms: 3x + -5(2 + 8x) = 18 + 2 3x + (2 * -5 + 8x * -5) = 18 + 2 3x + (-10 + -40x) = 18 + 2 Reorder the terms: -10 + 3x + -40x = 18 + 2 Combine like terms: 3x + -40x = -37x -10 + -37x = 18 + 2 Combine like terms: 18 + 2 = 20 -10 + -37x = 20 Solving -10 + -37x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -37x = 20 + 10 Combine like terms: -10 + 10 = 0 0 + -37x = 20 + 10 -37x = 20 + 10 Combine like terms: 20 + 10 = 30 -37x = 30 Divide each side by '-37'. x = -0.8108108108 Simplifying x = -0.8108108108
| 9n+2-n=3(n+9) | | 8(-6+2x)-3= | | 5x^2+20=20x | | 8w=8w | | 14x+5=14x+7-2 | | x=-3-6(0) | | -.4x-6(3x-2)=48.8 | | -5(n-3)=-n+27 | | 2x^2+3x+20= | | 6x-4=10X-24 | | -4y-(2y+5)=-(7+8y) | | 2-n=-6+4(2+5n) | | 4-(w-5)=2w-9 | | 6a-3(a+2)=3 | | 16n-15-4n=22-8n+3 | | 7(2y-9)-(y+6)= | | 6=10x-10+3x | | x+(2x)=126 | | -36=-18x-18y | | 5z-3+2z=18 | | 2x+2=6+6x | | 3x-8(-3-6x)=24 | | 24+3x=129 | | -0.2x+0.7x-3=-8 | | 3(2x+7y)=5x+24 | | -6=m+-3.42 | | 4-5x=6-6x | | -8(1-4n)-2n= | | =369x-3x | | 0.4x-2.5=0.6 | | -2(2-8b)= | | 5y+2-3=-3y+10y |